EXAMINATION OF THE POSSIBILITY OF ENHANCING THE PHYTOREMEDIATION POTENTIAL OF PLANTS THROUGH COMPLEXATION OF ALKALINE SOIL - Farzet Bikić; Muvedet Šišić; Sanela Beganović; Amira Pašalić; Adnan Mujkanovic; Aida Šapčanin; Vedran Stuhli; MIrnesa Čorbić; MIrnesa Čorbić; MIrnesa Čorbić (Journal of Sustainable Technologies and Materials, 2025)
This study presents the results of applied phytoextraction as a soil phytoremediation method, based on the analysis of selected heavy metal content in soil and plant material. The selected locations where phytoextraction was applied as a phytoremediation method (Gradišće, Podbrežje, and Tetovo) are situated in the city of Zenica, in proximity to the ArcelorMittal d.o.o. Zenica plant, identified as a potential major source of soil contamination in the surrounding area. The plant species used as potential phytoremediators were maize, Swiss chard, and alfalfa. The study analyzed the heavy metal content (Zn, Ni, Pb, Cd, Cr, and Cu) in soil samples after plant material extraction, as well as in the root samples of the plant material. Additionally, the study presents the pH values of the soil before sowing (initial state) and after plant extraction. The primary objective of this research was to determine whether soil complexation with an aqueous EDTA solution contributed to the increased uptake of selected heavy metals from soil into the selected plants under real environmental conditions. To assess this, one portion of the land plots was treated with a 0.1 M EDTA solution (from sowing until the late growth stage), while the other portion was left untreated. The results presented in this study indicate that soil complexation with the EDTA solution did not significantly enhance the phytoremediation potential of plants in the majority of analyzed samples. One of the key reasons for the reduced mobility of heavy metals from soil into plant material may be the alkaline nature of the soil at all three study locations, with a pH > 8. The mobility of heavy metals is significantly higher in acidic soils compared to alkaline soils.